Film and the Holocaust : new perspectives on dramas, documentaries, and experimental films - Kerner, Aaron (Continuum, 2011)
Machine generated contents note: 1.Introduction -- 2.The Realistic Imperative -- 3.The Holocaust as Dramatic Spectacle -- 4.Defiance and Resistance -- 5.Holocaust Comedies? -- 6.Sadism and Sexual Deviance -- 7.Body Genres I: Melodramatic Holocaust Films -- 8.Body Genres II: Pornography and Exploitation -- 9.Body Genres III: The Horror Genre and the Holocaust -- 10.Holocaust Documentaries I: Telling It Like It Really Was -- 11.Holocaust Documentaries II: Testimonials -- 12.Holocaust Documentaries III: Personal Documentaries -- 13.Holocaust Documentaries IV: The Poetic Documentary -- 14.Experimental Films I: Rituals of Memory -- 15.Experimental Films II: Lost and Found (Footage)